Water quality of the Iraqi southern marshes - Al-Saad, H.T.; Al-Hello, M.A.; Al-Taein , S.M.; DouAbul, A.A.Z. (Mesopotamian Journal of Marine Sciences, 2022)
After inundation, water quality surveys were designed and implemented during November 2005 to September 2006 at six locations, 4 in the Hor Al-Hammar (Al-Barga, Al-Nagara and Al-Baghdadia 1 and 2) the other 2 locations in Hor Al-Hwaaiza (Um Al-Warid and Um Al-Neiach). The sampling locations were selected to cover the distribution of the pollutants in these marshes. Physical and chemical stressors including the natural water quality parameters, dissolved oxygen (DO), biological oxygen demand (BOD), turbidity, total suspended solids (TSS), total dissolved solids (TDS), electrical conductivity (EC), total hardness (TH), temperature, salinity and pH as well as nutrients were studied. The mean range of the following parameters were recorded: pH (7.56-7.84), EC (1.29-3.22 mmohs/cm2), Ca (87.18-130.26 mg/l), Mg (60.35-111.17 mg/l), Cl (304.7-753.31 mg/l), TSS (11-38.58 mg/l), TDS (891-2040.42 mg/l), DO (5.16-10.05 mg/l), turbidity (4.57-39.03 FTU), salinity (0.53-1.7 ppt), water temperature (21.09-22.47 C°), air temperature (23.54-35.26 C°), SO4 (285.73-663.89 mg/l), HCO3 (204.39-255.22 mg/l), and TH (481.67-777.5 mg/l). These marshes are also rich in nutrient especially nitrate and phosphate which enhance their suitability for growth and billings of aquatic plants and phytoplankton. Also the seasonal variation of all the parameters were monitored during this study, and the result showed some fluctuation in some of them during different seasons at different locations of the marshes. The results obtained during this survey established important background information and a baseline for further restoration work and indicate reasonable signs of successful restoration.